Structural and Functional Properties of Subsidiary Atrial Pacemakers in a Goat Model of Sinus Node Disease - Soattin, Luca; Borbas, Zoltan; Caldwell, Jane; Prendergast, Brian; Vohra, Akbar; Saeed, Yawer; Hoschtitzky, Andreas; Yanni, Joseph; Atkinson, Andrew; Logantha, Sunil Jit; Borbas, Balint; Garratt, Clifford; et al. (Frontiers in Physiology, 2021)
Background The sinoatrial/sinus node (SAN) is the primary pacemaker of the heart. In humans, SAN is surrounded by the paranodal area (PNA). Although the PNA function remains debated, it is thought to act as a subsidiary atrial pacemaker (SAP) tissue and become the dominant pacemaker in the setting of sinus node disease (SND). Large animal models of SND allow characterisation of SAP, which might be a target for novel treatment strategies for SAN diseases. Methods A goat model of SND was developed (n=10) by epicardially ablating the SAN and validated by mapping of emergent SAPs location through an ablation catheter and surface electrocardiogram (ECG). Structural characterisation of the goat SAN and SAP was assessed by histology and immunofluorescence techniques. Results When the SAN was ablated, SAPs featured a shortened atrioventricular conduction, consistent with the location in proximity of atrioventricular junction. SAP recovery time showed significant prolongation compared to the SAN recovery time, followed by a decrease over a follow-up of 4 weeks. Like the SAN tissue, the SAP expressed the main isoform of pacemaker hyperpolarisation-activated cyclic nucleotide-gated channel 4 (HCN4) and Na+/Ca2+ exchanger 1 (NCX1), and no high conductance connexin 43 (Cx43). Structural characterisation of the right atrium revealed that the SAN was located at the earliest activation (i.e., at the junction of the superior vena cava with right atrium) and was surrounded by the paranodal-like tissue, extending down to the inferior vena cava. Emerged SAPs were localised close to the inferior vena cava and within the thick band of the atrial muscle known as the crista terminalis. Conclusions SAN ablation resulted in the generation of chronic SAP activity in 60% of treated animals. SAP displayed development over time and was located within the previously discovered PNA in humans, suggesting its role as dominant pacemaker in SND. Therefore, SAP in the goat constitutes a promising stable target for electrophysiological modification to construct a fully functioning pacemaker.